PENGEMBANGAN APLIKASI SI-BOOK UNTUPengembangan Aplikasi Si-Book Untuk Monitoring Dan Evaluasi Kinerja Pegawai Pada Modul Assignment Dengan Metode Iterative K MONITORING DAN EVALUASI KINERJA PEGAWAI PADA MODUL ASSIGNMENT DENGAN METODE ITERATIVE INCREMENTAL - Muhammad Ricky Chandra Dinata; Rahmat Fauzi; Ekky Novriza Alam (Jurnal Ilmiah Teknologi Informasi Asia, 2022)
In 2019 the world was affected by a coronavirus pandemic or Coronavirus Disease (Covid-19) which affected almost all daily work, the government took action to overcome this Covid-19 pandemic by Large-Scale Social Restrictions (PSBB) to Restrictions on Community Activities (PPKM). Badan Pengelola Pajak dan Retribusi (BPPRD) in Jambi City supports control of employee performance, but BPPRD in Jambi City still controls employee performance verbally, the tool is needed to solve this problem, therefore, application of monitoring and evaluation for employee performance control is developed that called SI-BOOK which is a website based using CodeIgniter Framework and the development method is iterative incremental. In Application Module of SI-BOOK was also developed to provide assignment as well as fill logbook. The iterative incremental method is a method that allows the users to see the results of the product that is being made and provide feedback during the development process, so this method is suitable for use by the SI-BOOK team. Testing on the SI-BOOK module assignment application uses the black-box testing method. Based on these tests, in the first phase iteration received feedback to add features. In the second phase iteration process did not get feedback and has met the needs so that the SI-BOOK application is applied to the server at BPPRD Jambi City and has been used to solve existing problems. In the future, the SI-BOOK application is recommended to add to the view assignment feature to implement the filter feature and display the ongoing assignment on the view logbook feature.